2020
DOI: 10.1051/0004-6361/202038228
|View full text |Cite
|
Sign up to set email alerts
|

The Villafranca catalog of Galactic OB groups

Abstract: Context. The spectral classifications of the Galactic O-Star Spectroscopic Survey (GOSSS) and the astrometric and photometric data from Gaia have significantly improved our ability to measure distances and determine memberships of stellar groups (clusters, associations, or parts thereof) with OB stars. In the near future, the situation will be further improved thanks to subsequent Gaia data releases and new photometric and spectroscopic surveys. Aims. We initiated a program to identify and determine the member… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 228 publications
3
20
1
Order By: Relevance
“…Both Cyg OB2 #8 and #22 have been traditionally treated as multiple stars but as already pointed out by Bica et al (2003), they should be considered as two clusters likely constituting the core of Cygnus OB2 and hosting the brightest stars of the area. A recent analysis by Maíz Apellániz et al (2020) has confirmed their cluster nature, and showed that both are at a distance of 1.7 kpc (the same distance as obtained by Berlanas et al 2019, see Sect. 4.5) and have similar proper motions.…”
Section: Binary Fractionsupporting
confidence: 77%
“…Both Cyg OB2 #8 and #22 have been traditionally treated as multiple stars but as already pointed out by Bica et al (2003), they should be considered as two clusters likely constituting the core of Cygnus OB2 and hosting the brightest stars of the area. A recent analysis by Maíz Apellániz et al (2020) has confirmed their cluster nature, and showed that both are at a distance of 1.7 kpc (the same distance as obtained by Berlanas et al 2019, see Sect. 4.5) and have similar proper motions.…”
Section: Binary Fractionsupporting
confidence: 77%
“…Regarding the star, the latest results from the Gaia mission 1 (Gaia Collaboration et al 2016;Collaboration et al 2020) provided the most accurate astrometric measurements to date: RA, Dec(J2000)= 20:33:36.076, +43:59:07.38; parallax Π = 0.582 ± 0.012 mas (thus d = 1.72 kpc); proper motions (µα cos δ, µ δ ) = (−2.59 ± 0.01, +0.73 ± 0.01) mas yr −1 . The distance we obtained is significantly larger than the value of 1.32-1.4 kpc typically used in the literature for this object; however, this value is in great agreement with the value of ≈ 1.7 kpc found more recently by other authors for Cyg OB2 (Berlanas et al 2019;Maíz Apellániz et al 2020).…”
Section: The Bow Shock Eb27 and The Star Bd+43 • 3654supporting
confidence: 89%
“…When studying a particular region, we recommend comparing the velocity and spatial distribution of the Hi-GAL sources with the systemic velocity of the region and its morphology, respectively. Finally, a path to improvement will be to update the distance (up to 4 kpc) of the nearby optical H ii regions and star forming regions (e.g., Cantat-Gaudin & Anders 2020; Zucker et al 2020;Maíz Apellániz et al 2020) used in the process and the inclusion of recent molecular cloud distance catalogs (such as Chen et al 2020), both based on the recent Gaia-DR2 data.…”
Section: Discussionmentioning
confidence: 99%